Psychological and behavioral impacts of early adult women victims of gaslighting behavior in romantic relationships - Sengkey, Marssel Michael; Illahibaccus-Sona, Shaima Banu (INSPIRA: Indonesian Journal of Psychological Research, 2024)
This study aims to identify and analyze the psychological and behavioral impact of early adult women who are victims of gaslighting in romantic relationships. Gaslighting is a behavior carried out by a gaslighter by intimidating, lying, dominating and manipulating victims where the goal is for the victims to doubt themselves, their memories, their own thoughts, and their own sanity. This study uses a qualitative research method with a case study approach. Subjects amounted to early adult woman who was a victim of gaslighting behavior in North Sulawesi, Indonesia. The data collection method used was observation and semi-structured interviews and then the data were analyzed using the data reduction process analysis method. The results showed that the psychological impacts experienced by victims of gaslighting behavior were confusion, frustration, anxiety, stress and low self-esteem. Meanwhile, the behavioral impact experienced by victims of gaslighting behavior is the emergence of argumentative behavior, desperate to convince the gaslighter, starting to doubt their own views, having difficulty making decisions, giving in and being silent to avoid conflict, and depending on the gaslighter.